EVALUASI GLUKOSA DARAH IKAN BATAK (Tor soro) PADA PADAT TEBAR BERBEDA - Pratama, Asep Rachmat; Supriyono, Eddy; Nirmala, Kukuh; Widiyati, Any (Universitas Teuku Umar, 2023)
This research was conducted with the aim to evaluate the performance of Batak fish (Tor soro) blood glucose in response to stocking density stress. Fish with an average of 2.21 g with a weight of 27 individuals were given stocking density stress by inserting them into 9 cylindrical containers of 200.96 cm2 and 3 L volume of peat water with stocking differently for 72 hours. These stocking density treatments consisted of A (2 fishes/0.02 m2), B (3 fishes/0.02 m2), C (4 fishes/0.02 m2) and E (5 fishes/0.02 m2) with three repetitions. Blood glucose was collected from 1 fish per container during 72 hours. The preliminary test was conducted to determine the oxygen demand of fish through the oxygen consumption level test, in which the oxygen demand from the fish was calculated in accordance to the density used. The average value of blood glucose levels of Batak fish that were given the stress of stocking density 2 fishes/0.02 m2, 3 fishes/0.02 m2, 4 fishes/0.02 m2, and 5 fishes/0.02 m2 tend to be low, as much as 53 mg/dL, 52.67 mg/dL, 49.33 mg/dL and 39.63 mg/dL respectively. The response of blood glucose to stocking density stress resulted in stocking recommendations for culture Batak fish ranging from 100-250 fish/m2 with 2,21-3,12 fish/ gram.